Análise da eficiência da biomassa de banana verde como complemento alimentar na melhora da constipação em pacientes funcionais e associada ao pós-operatório da Doença de Hirschdprung - Cassettari, Vanessa Mello Granado [UNESP] (2015)
Introduction: Constipation is an extremely common complaint in pediatrics and is increasingly on the rise. Painful bowel movements in 95% of cases, cause retentive posture, which can cause progressive distention of the rectum, which may lead to involuntary soiling. As an initial treatment, training and scheduling of evacuations and balanced diet is necessary. When there is no response to the treatment, it is essential to consider its organic form (5%), and Hirschsprung's disease is the most common diagnosis. Treatment is always surgical. However, postoperatively, some patients evolve with chronic constipation. The role of dietary fiber in the prevention and treatment has been discussed with frequency because of the health benefits. Resistant starch, found in some foods, such as in green bananas has been studied for potential benefits to human health. Because it is not digested and not absorbed in the small intestine, features similar to those of fiber behavior. The objective of this study was to evaluate the therapeutic efficacy of dietary supplementation of biomass of green banana in the treatment of chronic functional constipation and in patients with organic constipation associated with postoperative Hirschsprung's Disease. Patients and Methods: 34 patients divided into two groups were evaluated: G1- Constipated functional group (22 patients) and G2 - Group of patients in the postoperative Hirschsprung's disease with constipation (12 patients). The program took place for 9 consecutive weeks. The bowel function was assessed at two time points: 1 prior to the start of supplementation (M0) and after 8 weeks (M1) week by completing a questionnaire with the following variables: scale Bristol, days in the week with this evacuation, number of fecal leaks in the week, use and laxative dosage consumed. Patients consumed 2 tablespoons green banana biomass increased in the daily diet for 8 consecutive weeks. Results: With respect to the scale of ...